Bricoleurs extraordinaire: sports coaches in Inter War Britain. Issue 3 (2nd September 2019) - Day, Dave
ABSTRACT: In Inter-War Britain, several individuals exploited their athletic skills by pursuing careers as coaches, invariably drawing on, and reflecting on, their practical experiences, in a method theorised by John Dewey. These coaches were the masters of a body of specialist craft knowledge, the tacit nature of which was transmitted through apprentices watching the experts in action. Craft knowledge was never static, however, and coaches exemplified the notion of the "Bricoleur" in constantly trialling emerging knowledge, intuitively accepting or rejecting appropriate material. This paper explores how Inter-War practitioners utilised their coaching "toolbox", using examples from newspaper reports, personal and public archives, and instructional texts. The author chronicles some coaching lives and highlights the range of knowledge that coaches had at their command, well before the emergence of sports science and coach certification programmes. The paper concludes by questioning assumptions that coaches can no longer rely on "learning the trade" through experience.